Upaya Meningkatkan Hasil Belajar IPA melalui Model Pembelajaran Quantum Teaching Siswa Kelas V SD Negeri Pilahan Yogyakarta Tahun Pelajaran 2016/2017 - Septi Rahmawati (Universitas Sarjanawiyata Tamansiswa, 2017)
Abstract: The purpose of the research is to find out wether Quantum Teaching model can improve science achievement students of class V SD Negeri Pilahan Yogyakarta in the academic year of 2016/2017. It is an Classroom Action Research. The result shows improvement on students achievement. Prior to the study, the students achievement reaches 44% with average value 69. In the first cycle, reaches 62% with average value 75. More significantly,in the second cycle it reaches 87% with average value 87. In addition, the learning process 64% in first cycle and increase to 82% in the second cycle. It can be concluded that the Quantum Teaching model can improve students achievement and learning process.